Vietnam's Human Construction and Development to Meet the Requirements and the Policy of Industrialization and Modernization of the Country to 2030, Vision 2045 - Uoc, Tran Mai; Binh, Nguyen Thi Thanh (International Journal of Membrane Science and Technology, 2023)
Industrialization and modernization have been the cross-cutting goals of the Party and the State of Vietnam from the 3rd Congress to the present. To strive to be a developing country with modern industry and medium-high income by 2030, and by 2045 to become a developed country with high income, the promotion of industrialization and modernization, as well as the innovation of the growth model, and the restructuring of the economy, will be a crucial and transversal task in the coming years to build an economy which is modern, high-quality and sustainable development. The process of industrialization and modernization in Vietnam has gone through many stages of development with different traits. To achieve the goal of the formation of industrialization and modernization to 2030, vision 2045, besides the solutions related to the economic transformation; improving mobilization efficiency, developing human resources, promoting the improvement of institutions, creating a financial mechanism for localities to attract resources for development; forming appropriate policies to promote development …, Vietnam human construction and development to meet the requirements and the policy of industrialization and modernization of the country to 2030, vision 2045 is an urgent task both in theory and practice currently. The article is to analyze and clarify many fundamental issues related to Vietnam's human construction and development to meet the requirements and the policy of industrialization and modernization of the country to 2030, vision 2045 in Vietnam. As the result showed, The Party and Government of Vietnam have developed their thinking and awareness about industrialization and modernization, the fundamental challenges to Vietnam's human development in the process of industrialization and modernization of the country. The article also points out and analyzes the viewpoints and fundamental solutions to develop Vietnamese people to meet the requirements and the policy of industrialization and modernization of the country to 2030, vision 2045. The limitation of this article is that it still does not point out and analyze the factors affecting human construction and development to meet the requirements and the policy of industrialization and modernization of the country to 2030, vision 2045 in Vietnam.